Execution Models for Mobile Data Analytics - ur Rehman, Muhammad Habib; Batool, Aisha; Liew, Chee Sun; Teh, Ying Wah; ur Rehman Khan, Atta (Institute of Electrical and Electronics Engineers, 2017)
Execution models enable mobile data analytics applications to run on multiple platforms, but these applications need to handle massive heterogeneity. This article discusses various options for designing execution models and presents related challenges.